Integrated assessment of sediment metal pollution in Pb/Zn mining districts - Iñigo Moreno-Ocio; Pilar Rodriguez; Maite Martínez-Madrid; Leire Méndez-Fernández (Journal of Soils and Sediments, 2026)
Purpose This study assessed two Pb/Zn mining districts in northern Spain using a weight-of-evidence framework based on a reference condition approach integrating three lines of evidence (LOE): sediment chemistry, chronic sediment toxicity, and metal bioaccumulation in field biomonitors. Methods We studied seven sites in Arditurri ( n = 5) and Reocín ( n = 2). In the absence of Spanish sediment quality guidelines, ecological backgrounds and thresholds for Cd, Pb, and Zn were derived from 31 to 55 reference sites across northern Spain. Toxicity was measured with a 28-day Tubifex tubifex whole-sediment bioassay; effective tissue residues were also obtained from laboratory tests. An overall weight-of-evidence approach was performed based on alterations measured across the three LOEs. Results The proposed ecological thresholds for Cd, Pb, and Zn are comparable to values reported for other regions. Sediment Cd, Pb, and Zn exceeded background by more than six to ten times across mining sites. All three lines of evidence indicated impairment driven by sediment chemistry and chronic toxicity at all test sites, and hazardous bioaccumulation levels were not reached at only one site. Conclusions Ecological Thresholds represent a useful tool for pollution assessment in mining areas. Concordant evidence from chronic toxicity tests and biomonitor´s effective residues indicate sediment-borne metals pose risk to benthic communities and ecological integrity through toxicity and bioaccumulation at most sites. Effective tissue residues obtained here are relevant candidates for deriving environmental quality standards. Overall, the assessment supports implementing management actions to reduce metal sources at these sites.

Metals and metalloids in high-altitude Pyrenean lakes: sources and distribution in pre-industrial and modern sediments - Azibar Rodriguez-Iruretagoiena; Ainara Gredilla; Silvia Fdez-Ortiz de Vallejuelo; Gorka Arana; Maite Meaurio; Juan Manuel Madariaga; Jean Christophe Auguet; Aridane González González; Oleg S. Pokrovsky; Luis Camarero; Alberto de Diego (Environmental Science and Pollution Research, 2023)
High-altitude Pyrenean lakes are ecosystems far from local pollution sources, and thus they are particularly sensitive to the atmospheric deposition of metals and metalloids. This study aims to quantify the effect of human activity in 18 lakes located in both side of the France–Spain frontier. Sediment cores were collected in summer 2013, sampled at a 1cm resolution and the concentration of 24 elements was measured by ICP-MS. Statistic and chemometric analysis of the results highlights the influence of the geographical position and lithogenic features of each lake basin on trapping pollutants. More than the 80% of the lakes showed values of enrichment factor (EF) above 2 for at least one of the elements investigated in at least one core interval, which corroborates the existence of historical anthropogenic inputs of elements in the studied area. The results demonstrate the natural origin of As and Ti in Pyrenees, together with the significant anthropogenic inputs of Cd, Pb, Sb and Sn from ancient times. The data set points mining activities as the main historical source of pollution and illustrate the large impact of the industrial revolution. The regional variability could reflect also differential long-range transport, followed by dry or wet deposition.

Examining the Ability of CMIP6 Models to Reproduce the Upwelling SST Imprint in the Eastern Boundary Upwelling Systems - Rubén Varela; Maite DeCastro; Laura Rodriguez-Diaz; João Miguel Dias; Moncho Gómez-Gesteira (Journal of Marine Science and Engineering, 2022)
Knowing future changes in the sea surface temperature (SST) is of vital importance since they can affect marine ecosystems, especially in areas of high productivity such as the Eastern Boundary Upwelling Systems (EBUS). In this sense, it is key to have fine resolution models to study the SST patterns as close as possible to the coast where the upwelling influence is greater. Thus, the main objective of the present work is to assess the ability of 23 General Circulation Models (GCMs) from phase six of the Coupled Model Intercomparison Project (CMIP6) in reproducing the upwelling SST imprint in the EBUS through a comparison with the Optimum Interpolation of Sea Surface Temperature (OISST ¼) database of the National Oceanic and Atmospheric Administration for the common period of 1982–2014. The results have shown that most of the CMIP6 GCMs overestimate nearshore SST for all the EBUS with the exception of Canary. Overall, the models with better resolution showed lower Normalized Root Mean Squared Error (NRMSE) and Normalized Bias (NBias), although the ability of the models is dependent on the study area. Thus, the most suitable models for each EBUS are the CNRM-HR, GFDL-CM4, HadGEM-MM, CMCC-VHR4, and EC-Earth3P for Canary; CESM1-HR, CMCC-VHR4, ECMWF-HR, and HadGEM-HM for Humboldt; and HadGEM-HH and HadGEM-HM for California. In the case of Benguela, no model adequately reproduces the SST imprint under the conditions established in the present study.

Monocyte-to-Lymphocyte Ratio in Clot Analysis as a Marker of Cardioembolic Stroke Etiology - Jesús Juega; Carlos Palacio-Garcia; Maite Rodriguez; Matias Deck; David Rodriguez-Luna; Manuel Requena; Álvaro García-Tornel; Noelia Rodriguez-Villatoro; Marta Rubiera; Sandra Boned; Marian Muchada; Marc Ribo; et al. (Translational Stroke Research, 2022)

Developing As and Cu Tissue Residue Thresholds to Attain the Good Ecological Status of Rivers in Mining Areas - Iñigo Moreno-Ocio; Leire Méndez-Fernández; Maite Martínez-Madrid; Noemí Costas; Isabel Pardo; Pilar Rodriguez (Archives of Environmental Contamination and Toxicology, 2022)
The study was performed on residue-effects datasets from polluted and unpolluted sites in the Nalón River basin (northern Spain). The effects were measured in terms of alteration of field macroinvertebrate communities, and measured as ecological status scores, and number of families and abundance of Ephemeroptera, Plecoptera and Trichoptera (EPT). Non-linear regression models of the field-measured tissue residues in 10 taxa related to the ecological status of the macroinvertebrate communities were used to derive effective tissue residues (ERs). These were estimated for the good/moderate boundary defined by the ecological quality ratio (EQRs) score and for the 50% reduction of EQR and EPT metrics. As, Cu, Hg and Se ERs were calculated for several macroinvertebrate taxa with different feeding styles. The ER dataset allowed us to estimate As and Cu hazardous concentrations (HC), using species sensitivity distribution models, and were interpreted as community thresholds. Further studies for Hg and Se are needed to complete the database required for HC estimation. The reliability and differences of the several thresholds were tested in a risk assessment using a tissue-residue approach (TRA) conducted with field organisms from Cauxa Creek, a tributary from the same basin exposed to high levels of metals in the sediments due to gold mining activities. This risk assessment identified that As and Cu tissue residues satisfactorily explained the reduction in the ecological status of the macroinvertebrate assemblages. Our results indicate that TRA can help in setting future environmental quality standards for the protection of aquatic biota. Graphical Abstract

Predicting Atrial Fibrillation with High Risk of Embolization with Atrial Strain and NT-proBNP - Jorge Pagola; Jesus Juega; Jaume Francisco-Pascual; Alejandro Bustamante; Anna Penalba; Elena Pala; Maite Rodriguez; Mercedes De Lera-Alfonso; Juan F. Arenillas; Juan Antonio Cabezas; Francisco Moniche; Reyes de Torres; et al. (Translational Stroke Research, 2021)

Heavy metal concentration in feathers of Little Egret (Egretta garzetta) nestlings in three coastal breeding colonies in Spain - Iratxe Rubio; Maite Martinez-Madrid; Leire Méndez-Fernández; Aitor Galarza; Pilar Rodriguez (Ecotoxicology, 2016)

Analysis of the most important river plumes on the Atlantic and Mediterranean Iberian coast by means of satellite imagery - Novoa Diego; Mendes Renato; Rodriguez Maite; Dias João Miguel; Gesteira Ramón (Frontiers in Marine Science, 2014)

Toxicity and critical body residues of Cd, Cu and Cr in the aquatic oligochaete Tubifex tubifex (Müller) based on lethal and sublethal effects - Leire Méndez-Fernández; Maite Martínez-Madrid; Pilar Rodriguez (Ecotoxicology, 2013)

Ecotoxicological assessment of effluents in the Basque country (Northern Spain) by acute and chronic toxicity tests using Daphnia magna straus - Pilar Rodriguez; Maite Martinez-Madrid; Adolfo Cid (Ecotoxicology, 2006)

Selective feeding by the aquatic oligochaete Tubifex tubifex (Tubificidae, Clitellata) - Pilar Rodriguez; Maite Martinez-Madrid; Jesús Angel Arrate; Enrique Navarro (Hydrobiologia, 2001)

Sediment Toxicity Bioassays for Assessment of Contaminated Sites in the Nervion River (Northern Spain). 2. Tubifex tubifex Reproduction Sediment Bioassay - Maite Martinez-Madrid; Pilar Rodriguez; Juan Ignacio Perez-Iglesias; Enrique Navarro (Ecotoxicology, 1999)